La creatividad y su incidencia en el proceso de enseñanza y aprendizaje en el área de lengua y literatura en la Unidad Educativa Juan Montalvo en el periodo lectivo 2023-2024 del Cantón Baba - Fuentes Villavicencio, Narcisa Alexandra (2023)
Creativity allows students to express themselves in a unique and original way, which enriches their writing and communication skills, and helps them better analyze and understand literary texts. The objective was to determine the incidence of creativity in the teaching and learning process in the area of Language and Literature in the Juan Montalvo Educational Unit in the 2023-2024 school year of the Baba canton. The methodology is quantitative, with a non-experimental, descriptive design, with a correlational scope, the statistical analysis allowed testing the hypotheses, we worked with a sample of 45 students and a teacher from the seventh grade of Basic. Results, 55% of students do not play word games and riddles, 49% indicated that the teacher does not help them develop creativity through the use of techniques, 40% do not know how to create a different ending in stories, 47% feel unmotivated when starting Language and Literature classes, 56% indicated that the content applied by the teacher sometimes helps them in reading comprehension, 100% would like teachers to use educational platforms more frequently for teaching language and Literature, teachers consider that the use of digital tools provides an interactive, dynamic and participatory learning experience for students. It is concluded that creativity has a positive impact in the area of language and literature, since it encourages personal expression, critical thinking, literary creation and the enjoyment of reading.